Analysis of the Pancreatic Cancer Microbiome Using Endoscopic Ultrasound–Guided Fine-Needle Aspiration–Derived Samples. Issue 4 (12th April 2022) - Nakano, Shintaro; Kawamoto, Yasuyuki; Komatsu, Yoshito; Saito, Rika; Ito, Ken; Yamamura, Takahiro; Harada, Kazuaki; Yuki, Satoshi; Kawakubo, Kazumichi; Sugiura, Ryo; Kato, Shin; Hirata, Koji; et al.
Abstract : Objectives: Most previous studies have analyzed bacteria in tumors using resected pancreatic cancer (PC) tissues, because it is difficult to obtain tissue samples from unresectable advanced PC. We aimed to determine whether minimal tissue obtained by endoscopic ultrasound–guided fine-needle aspiration is useful for microbiome analysis. Methods: Thirty PC and matched duodenal and stomach tissues (N = 90) were prospectively collected from 30 patients who underwent endoscopic ultrasound–guided fine-needle aspiration. Bacterial DNA was extracted, and 16S rRNA sequencing was performed. The primary outcome was the success rate of bacterial detection in tumors. Bacterial diversity and structure were investigated. Results: The bacterial detection rates were 80%, 100%, and 97% in PC, gastric, and duodenal samples, respectively. Pancreatic cancer tissues showed a lower α-diversity and a significantly different microbial structure than stomach and duodenal tissues. Proteobacteria were more abundant, whereas Firmicutes, Bacteroidetes, and Fusobacteria were less abundant in PC tissues than in stomach and duodenal tissues. Acinetobacter was more abundant in PC tissues than in stomach and duodenal tissues, and Delftia was more frequently detected in resectable PC. Conclusions: Endoscopic ultrasound–guided fine-needle aspiration samples were valuable for PC microbiome analysis, revealing that the bacterial composition of PC is different from that of the stomach and duodenum.